Criminal justice research and practice: diverse voices from the field - Miller, Susan L. (The Northeastern series on gender, crime and law, 2007)
Foreword / by Claire M. Renzetti -- Editor's preface and acknowledgments -- Ways to inquire: research methods -- Introduction: from passion to practice / Joanne Belknap and Hillary Potter -- Feminist research methods in theory and action: learning from death row exonerees / Saundra D. Westervelt and Kimberly J. Cook -- Dispatches from the field: negotiating difference and diversity in criminological research / Shana L. Maier and Brian A. Monahan -- Inquirers: professionals, activists, and researchers -- "Comforting the troubled and troubling the comfortable": reflections on lawyering for the poor / Daniel Atkins and Eliza Patten -- When the stakes are life and death: the promise and peril of public sociology for capital cases / Jill McCorkel -- Getting from here to there: a guide for aspiring academics / Susan Caringella and Drew Humphries -- Diversifying the research enterprise: experiences of African American women working in a federal research agency / Angela Moore-Parmley and Jocelyn Fontaine -- Sites of inquiry: topics and samples -- Changing my life, among others: reflections on the life and work of a feminist man / Walter S. Dekeseredy -- Managing a man's world: the experiences of a female probation officer in a male sex offender supervision unit / Michelle L. Meloy -- Diversity in blue: lesbian and gay police officers in a masculine occupation / Susan L. Miller, Kay B. Forest, and Nancy C. Jurik -- "This isn't about us": benefits of dog -- Training programs in a women's prison / Dana M. Britton and Andrea L. Button -- Epilogue -- Criminal justice, gender, and diversity: a call for passion and public criminology / Meda Chesney-Lind -- Contributors' biographies -- Index